2014
DOI: 10.1177/0363546514536843
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Clinical Characteristics of Osteochondritis Dissecans of the Humeral Capitellum Among Adolescent Baseball Players

Abstract: The prevalence of OCD of the humeral capitellum, including latent cases, was 3.4% among adolescent baseball players. Players with OCD lesions began playing baseball at earlier ages, had played for longer periods, and had experienced more elbow pain. The player's current baseball position may not be related to the existence of OCD lesions in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
111
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 28 publications
0
111
1
4
Order By: Relevance
“…En cambio,fue ampliamente tratada por la literatura clínica del comportamiento corporal de los deportistas (e.g. Kida et al 2014;Matsuura et al 2014) debido a que las lesiones en esta articulación suelen estar asociadas con el movimiento de lanzamiento (Guerra y Timmerman 1996). En este caso se trata de un individuo masculino, con dieta predominantemente terrestre.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En cambio,fue ampliamente tratada por la literatura clínica del comportamiento corporal de los deportistas (e.g. Kida et al 2014;Matsuura et al 2014) debido a que las lesiones en esta articulación suelen estar asociadas con el movimiento de lanzamiento (Guerra y Timmerman 1996). En este caso se trata de un individuo masculino, con dieta predominantemente terrestre.…”
Section: Discussionunclassified
“…Estos últimos explicarían la alta prevalencia de este tipo de lesiones en atletas de alto rendimiento (Aichroth 1971;Cahill 1995;Takahara et al 1999). Por ejemplo, puede alcanzar entre un 2,1% (Matsuura et al 2014) y un 3,4% en la tróclea del húmero en jugadores de béisbol (Kida et al 2014). En cambio, en poblaciones no asociadas con la actividad física deportiva las frecuencias de OCD son menores, alcanzando por ejemplo entre un 0,01 y un 0,06% en el caso de la rodilla (Lindén 1976;Petersen et al 2006;Solomon et al 2010).…”
Section: Terminología Patogénesis Y Epidemiología General De La Ocdunclassified
“…We believe that our data coincide with a growing body of evidence that pain and injury in the young thrower is more closely related to the cumulative number of throws throughout the course of a year rather than the number of pitches in a given game or season. 5,6,9,10 In their position statement for youth baseball players, The American Sports Medicine Institute recommend that youth pitchers not participate in competitive pitching for at least 4 months per year, and that they should not perform overhead throwing of any kind for at least 2 to 3 months per year, with 4 being preferred. 1 In our cohort, nearly 70% of players were year-round players, violating this recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…US imaging has been used to diagnose early COCD without elbow pain and to provide an opportunity for conservative treatment 2, 12. Kida et al also used US imaging to investigate the prevalence of COCD among junior high‐school and high‐school baseball players who rarely visit medical institutions because of being minimally symptomatic 13. Takahara et al reported US criteria that distinguish between stable and unstable COCD lesions for patient management decisions.…”
Section: Introductionmentioning
confidence: 99%